Retrieval of Images Using SVM - Shiral, J. V.; Burman, Munmun; Bhadbhade, Apurva; Patil, Dhanashree; Motghare, Kajal; Wanjari, Neha (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
Image retrieval is a technique which is used to search and retrieve images from a large database of digital images. Content-based image retrieval (CBIR) is a technique which allows searching images from large scale image database based on contents as needed by user.This paper introduces a technique to retrieve images by classifying it on the basis of the features and characteristics it contains using Support Vector Machine (SVM). The dataset of images is created which is used for feature matching purpose by SVM to find similar images from the database and based on user requirements images are retrieved.